QUALITY CULTURE DEVELOPMENT MODEL IN STATE ELEMENTARY SCHOOL-TENGGARONG - Baharuddin,; Usman, Husaini; Rachmad, Edi; Sjamsir, Hasbi (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to find a model for developing a quality culture in State Elementary School - 02 Tenggarong. This research used a qualitative approach with a phenomenological type. Data was collected through participant observation, in-depth interviews, and documentation. The research instrument is the researcher himself. Key people are the principal, the teacher, and the school supervisor. Data were analyzed using the Miles and Huberman interactive model. Data validity is through credibility, transferability, dependability, and confirmability.This research found: (1) School quality culture is a superior school in PBM, MBS, and extracurricular; the meaning is in accordance with the results of the quality culture guidance; (2) Quality culture indicators are the implementation of the seven pillars of MBS effectively and efficiently; the meaning is in accordance with the results of the quality culture guidance; (3) there are five steps of quality culture; the meaning is in accordance with the experience at school; (4) there are seven factors supporting quality culture; the meaning is in accordance with the experience at school; (5) there are five factors that inhibit quality culture; the meaning is in accordance with the experience at school; (6) there are eight steps to overcome the inhibiting factors of quality culture; the meaning is in accordance with the experience at school; and (7) there are four ways to develop a quality culture; the meaning is according to experience in school.